2000
DOI: 10.1192/bjp.176.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Unpublished rating scales: A major source of bias in randomised controlled trials of treatments for schizophrenia

Abstract: Unpublished scales are a source of bias in schizophrenia trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
166
1
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 821 publications
(180 citation statements)
references
References 6 publications
(7 reference statements)
1
166
1
8
Order By: Relevance
“…38 Further, the effect estimates decreased as the proportion of relevant studies contributing to the meta-analysis increased. Other research has investigated discrepancies due to unpublished versus published scales 39 and handling of baseline and end-point data. 40 …”
Section: Selective Outcome Reportingmentioning
confidence: 99%
“…38 Further, the effect estimates decreased as the proportion of relevant studies contributing to the meta-analysis increased. Other research has investigated discrepancies due to unpublished versus published scales 39 and handling of baseline and end-point data. 40 …”
Section: Selective Outcome Reportingmentioning
confidence: 99%
“…The decision in favor of an instrument may have important consequences. Marshall et al [1] showed that in schizophrenia trials authors were more likely to report that treatment was superior to control when an unpublished instrument was used in the comparison, rather than a published instrument. Furthermore, the selection of instruments with good measurement properties will lead to the detection of smaller treatment effects, or more power to draw stronger conclusions, and therefore to better interpretation of study results.…”
Section: Introductionmentioning
confidence: 99%
“…It was our aim (1) to find all existing systematic reviews of measurement properties, (2) to appraise the quality of the review process of these reviews, (3) to describe if and how the authors of reviews assessed the methodological quality of the primary studies included in these reviews, (4) to describe if and how the authors of reviews evaluated the results of the primary studies, and (5) to describe if authors of reviews synthesized the above-mentioned data (steps 3 and 4) to come to an overall conclusion regarding the quality of each instrument.…”
Section: Introductionmentioning
confidence: 99%
“…In social and psychological intervention studies, outcome measures are often subjective, variables may relate to latent constructs, and information may come from multiple sources (for example, participants or providers). While it is an issue in other areas of research, the influence on RCT results of the quality of subjective outcome measures in social and psychological intervention research has long been highlighted, given their prevalence in social and psychological intervention research [43]. Descriptions of the validity, reliability, and psychometric properties of such measures are therefore particularly useful for social and psychological intervention trials, especially when they are not widely available or discussed in the research literature [26,44].…”
Section: Aspects Of Internal Validitymentioning
confidence: 99%